2022
DOI: 10.1021/acs.energyfuels.2c01805
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Theoretical Modeling of Suitable Co-precipitation Conditions for Producing NMC111 Cathode Material for Lithium-Ion Batteries

Abstract: Lithium nickel manganese cobalt oxide (NMC111) is considered to be one of the most promising cathode materials for commercial lithium-ion battery (LIB) fabrication. Among the various synthesis procedures of NMC111, hydroxide co-precipitation followed by lithiation is the most cost-effective and scalable method. Physical and chemical properties of the co-precipitation product such as yield, particle size, morphology, and tap density, depend upon the various reaction parameters, which include pH, chelating agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Our group has recently performed theoretical modeling on the effect of NH 4 OH concentration and pH on the yield of NCM111 by the hydroxide co-precipitation method. 25 It was observed that the precursor synthesized at a pH of 11.8 and NH 4 OH concentration of 0.1 M had the highest tap density. The modeling of the co-precipitation process relies on the solution of the mass action equations for the reversible reactions of all components in the aqueous phase, including dissociation of primary process inputs and formation of hydroxide and ammonia complexes with each of the transition metals.…”
Section: Co-precipitationmentioning
confidence: 97%
“…Our group has recently performed theoretical modeling on the effect of NH 4 OH concentration and pH on the yield of NCM111 by the hydroxide co-precipitation method. 25 It was observed that the precursor synthesized at a pH of 11.8 and NH 4 OH concentration of 0.1 M had the highest tap density. The modeling of the co-precipitation process relies on the solution of the mass action equations for the reversible reactions of all components in the aqueous phase, including dissociation of primary process inputs and formation of hydroxide and ammonia complexes with each of the transition metals.…”
Section: Co-precipitationmentioning
confidence: 97%
“…In this approach, TM sulfates and lithium hydroxide were the starting materials. A stoichiometric quantity of TM sulfates (8:1:1) was selected and mixed with DI water to create a solution composed of NiSO4•6H2O 1.6 M, MnSO4•H2O 0.2 M, and CoSO4•7H2O 0.2 M [16]. An alkaline solution was prepared mixing 180 mL of DI water, 18 mL of NH4OH 1.5 M, and 0.333 mL of NaOH 4 M in a three-necked round flask.…”
Section: Cpt Approachmentioning
confidence: 99%
“…Different experimental and modeling approaches for thermal runaway (TR) detection along with the need for the development of a battery management system have been emphasized in this paper. Mugumya et al 7 performed theoretical modeling to determine suitable synthesis conditions for lithium nickel manganese cobalt oxide (NMC111) cathode material through hydroxide co-precipitation. Experimental synthesis of the three metal hydroxide precursors with different tap densities using low ammonia concentrations to assess the theoretical model was undertaken.…”
Section: Review the Co-gasification Ofmentioning
confidence: 99%